Understanding the Link of Knowledge Management and Organizational Performance - Elisa Elman Braganza (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Knowledge management nowadays becoming a huge area in terms of managing in any organization that closely related to human resources, organizational development, change management, information technology, brand and reputation management, performance measurement, and evaluation. The emergence of knowledge management in light of the very dynamic workforce in the hospitality industry especially in developing states ignites the need to understand its role. Thus, this study aims to discover the relationship of knowledge management and employee commitment in the hospitality industry so organizations can devise a good HR plan most especially for committed employees. Design/methodology/approach: This study was done in Davao Region, Philippines with 450 employees from the various sectors of the hospitality industry using a survey method. Findings: Empirical findings revealed that knowledge management and organizational commitment are of high levels are described by the respondents. Further, knowledge management and organizational commitment are significantly correlated with each other which implies significant role in the developing and molding skillful and committed employees in the hospitality industry. Paper type: Research paper